ANALYSIS OF GASTRONOMIC TOURISM VILLAGE PLANNING IN CISAMBENG VILLAGE, SUB-DISTRICT PALASAH, MAJALENGKA REGENCY - Muhamad Fikriyananda; Rini Andari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Cisambeng Village, is one of the villages with the potential of a tourism village owned by Majalengka Regency. This cisambeng village has almost 80% of its population as producers and sellers of processed soybeans which are a concern and can be used as a gastronomic tourism object and artificial tourism as a result of the village's potential commodities. This potential has not been utilized and developed by the local community until now. This study aims to explore the potential that exists in the Cisambeng village area and to find and develop the most suitable tourism development model for the Cisambeng area. The obstacles found in the field relate to the development of the model of the tourist village, from the aspect of attractiveness, accommodation, accessibility, and amenities. This study was analyzed using a qualitative approach method with data collection carried out in two ways, namely interviews and Focus Group Discussion. Based on the review and analysis conducted regarding the characteristics, potential, problems in the field, a model with a SWOT analysis so as to have implications for the environment and the village community so that it can strengthen tourism development in a sustainable manner.